Desenvolvimento de um brinquedo apoio de baixo custo para o ensino de lógica de programação a crianças - BRUNA CRISTHINE AMARILHA TELES (2024)
This work presents the development of Brumu, an educational kit designed to promote Computational Thinking (CT) in children aged 3 to 9. Inspired by the Cubetto educational robot, but with a significantly lower cost, Brumu combines a mobile application and a robot built with widely available components. The solution aims to democratize access to educational robotics, aligning with the principles outlined in Brazil's National Common Curricular Base (BNCC), which emphasizes the importance of CT in basic education. The app, built with MIT App Inventor, is easy to use and allows kids to program the robot by dragging and dropping commands onto the screen. The bluetooth-controlled robot was built with an Arduino UNO and other components that are cheaper and easier to assemble. Brumu offers a hands-on, fun experience that helps kids learn programming while developing creativity, logical reasoning, and problem-solving skills. Through this project, Brumu was successfully developed at approximately 91.76% lower cost than Cubetto, accompanied by a detailed manual for assembly and use. This kit represents a scalable and accessible alternative for educational institutions, paving the way for broader adoption of robotics in early education. Future work includes extending the platform with subject-specific maps, lesson plans and usability testing to further enhance its application in diverse educational contexts.